Efektivitas Tanggung Jawab Sosial Perusahaan Pada PT. Indah Kiat Pulp and Paper Tbk Perawang Kecamatan Tualang Kabupaten Siak - Herman Herman; Lilis Suriani; Elfa Wesinah BR Gultom (Universitas Serang Raya, 2023)
The problems that arise in relation to this research are that in the context of implementing corporate social responsibility, it has not been running effectively, which is marked by the lack of precise targeting of the assistance provided in the context of community empowerment by PT. Indah Kiat Pulp and Paper Tbk Perawang to farmers in Tualang District. In addition, the low nominal assistance provided is also an obstacle for local community empowerment programs. In addition, the assistance provided will be returned to the company is also an unusual thing. The purpose of this study was to analyze and explain the effectiveness of corporate social responsibility at PT. Indah Kiat Pulp and Paper Tbk Perawang in Tualang District, Siak Regency. The type of research used is qualitative research with descriptive method. There are two types and sources of data, namely primary data and secondary data. Data collection techniques consist of interviews, observation and documentation. Informants from this research consisted of the Chief Executive of CSR, Head of the TJSP Forum Unit of Bappeda Siak, Coordinator of Agricultural Extension Center in Tualang District and community elements as fostered farmers. The results showed that of the 5 indicators, namely understanding of the program, right on target, on time, achieving goals and real changes had not run effectively. The obstacle faced is that there has not been a collaboration between PT. IKPP, Center for Agricultural Extension and Assisted Farmers. In the future, it is hoped that there will be good cooperation between the parties involved, and that each CSR program activity is free of charge or free, and the CSR forum shows its performance in accordance with applicable regulations.